KONSERVASI LAHAN PERTANIAN BERBASIS EKOLOGI DI KAWASAN DATARAN TINGGI DIENG WONOSOBO - Kristiyanto Kristiyanto; Riajeng Kristiana; Netty Demak H Sitanggang (Universitas Muhammadiyah Semarang, 2018)
Doing of farmland restoration a part of conservation process to agriculture transformation pattern of ecological paradigm which there is to expect balance of ecosystem in farming, this case as response on appear to complex of farming problem occurrence. That phenomena has been caused of accumulated processing in used to pesticide medicine did, which it has disturbance of farming ecosystem event. Collaboration and elaboration approach has used to data collect methods which depth interview process and Focusing of group discussion (FGD) has become of one all of steps for understanding of problem that deal of farmers, in bridging of farming problem complex of contemporary. Empirically of result this research showed with literature review of support, that farmer’s dependence of agriculture technology modern package (Greenrevolution paradigm) indirectly or directly, it has omitted of farmer’s selfsupporting in managing of farmland by creative, innovative, and wisdom, therefor the need of evalution process between farmers, scientist, and academician in developing of agriculture system by conservation. The problem of farmers at this moment has become of opportunities and challenges next years, so this needs to elaboration and to collaboration process continually, in order to agroecosystem model by dynamic and sustainable. Keywords: Agriculture system, Green revolution, Local wisdom, Restoration process